2021
DOI: 10.19088/k4d.2021.001
|View full text |Cite
|
Sign up to set email alerts
|

Linking Business Environment Reform with Gender and Inclusion: A Study of Business Licensing Reform in Indonesia

Abstract: Business environment reform (BER) targets inadequate business regulations. It is intended to remove constraints to business investment, enabling growth and job creation, and create opportunities for international business to contribute to and benefit from this growth. However, there is a lack of detailed knowledge of the impact of BER on gender and inclusion (G&I). While a review of existing literature suggests that in general, there is no direct link between BER and G&I, indirect links are likely thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It also demonstrated an increase in medium and large firms, with these increases marginally favouring women over men outside of Jakarta. However, the reform had no significant effects on employment (Saha et al, 2021).…”
Section: Business Registration Reforms In Indonesiamentioning
confidence: 84%
See 1 more Smart Citation
“…It also demonstrated an increase in medium and large firms, with these increases marginally favouring women over men outside of Jakarta. However, the reform had no significant effects on employment (Saha et al, 2021).…”
Section: Business Registration Reforms In Indonesiamentioning
confidence: 84%
“…However, one study which assessed whether the reform encouraged formalisation found little evidence that the programme reduced the rates of informality (Rothenberg et al, 2016). Recent research analysing World Bank Enterprise Survey data demonstrates that this reform had impacts which varied by geography, and by gender (Saha et al, 2021). Overall, in regions where the reform was implemented effectively, there was an increase in firm performance.…”
Section: Business Registration Reforms In Indonesiamentioning
confidence: 99%
“…The view that BERs are gender neutral has been disputed, with compelling evidence that women experience the business environment very differently from men (despite there being no legal discrimination between the two in most countries), with potentially different BER outcomes for men and women (Aidis 2017;Saha et al 2021). In response, gender-sensitive BERs have been proposed, which refer to 'changes in policy, legal, institutional, and regulatory conditions that govern business activities in ways that account for the dynamics of socially constructed relationships between men and women' (Miles 2017: 4).…”
Section: Business Environment Reforms and Gendermentioning
confidence: 99%
“…Women who are not wage earners but who are business owners or own-account producers (e.g. women-led small and medium-sized enterprises (SMEs)), find it difficult to become independently involved in global value chains (Saha et al 2021). This is because these women often lack access to the productive resources and networks needed to achieve competitive advantage.…”
Section: Empirical Evidence On Employment Effectsmentioning
confidence: 99%